Mixed Effects Models for Resampled Network Statistics Improves Statistical Power to Find Differences in Multi-Subject Functional Connectivity - Narayan, Manjari; Allen, Genevera I. (Frontiers in Neuroscience, 2016)
Many complex brain disorders such as Autism Spectrum Disorders exhibit a wide range of symptoms and disability. To understand how brain communication is impaired in such conditions, functional connectivity studies seek to understand individual differences in brain network structure in terms of covariates that measure symptom severity. In practice, however, functional connectivity is not observed but estimated from complex and noisy neural activity measurements. Imperfect subject network estimates can compromise subsequent efforts to detect covariate effects on network structure. We address this problem in the case of Gaussian graphical models of functional connectivity, by proposing novel two-level models that treat both subject level networks and population level covariate effects as unknown parameters. To account for imperfectly estimated subject level networks when fitting these models, we propose two related approaches --- R^2 based on resampling and random effects test statistics, and R^3 that additionally employs random adaptive penalization. Simulation studies using realistic graph structures reveal that R^2 and R^3 have superior statistical power to detect covariate effects compared to existing approaches, particularly when the number of within subject observations is comparable to the size of subject networks. Using our novel models and methods to study parts of the ABIDE dataset, we find evidence of hypoconnectivity associated with symptom severity in Autism Spectrum Disorders, in frontoparietal and limbic systems as well as in anterior and posterior cingulate cortices.